Boundary Devices for Reflexive Teachers - Nadia Sansone; Manuela Fabbri; Ilaria Bortolotti (MDPI AG, 2024)
Reflexivity appears to be a key focus when designing teachers' training; therefore, designers and trainers need to plan and put in place situated and proactive learning contexts in which reflexivity is supported by specific participatory devices. During a 1st level master's degree for teachers and educators, based on the Trialogical Learning Approach, learners are involved in several collaborative activities to create meaningful objects. Divided into 14 groups of four members covering specific roles (the coordinator, the researcher, the storyboarder, and the diarist), the participants collaboratively built a multimedia teaching resource about a chosen methodological-didactic theme. Applying a qualitative approach, this study analyzes the online diaries compiled during the activity to understand its impact as a "meta" boundary object able to support reflexivity on one's professionalism. The content analysis focused on analyzing how objects and practices enabled learning and participation and how students' identity evolved during group work. The results show that a diary may act as a reflexive tool, allowing for the externalization of the processes that underly the construction of individual and collective knowledge and promoting reflection on practices and identity positioning within a community composed of professionals working in educational fields. In the end, practical implications and recommendations are provided to enhance the reflexive diaries both in teachers' training and in the daily practice with students.